BENTURAN ANTAR PERADABAN (CLASH OF CIVILIZATION) DALAM PERSIAN WAR 490 BC-480 BC - admin Wisnu istoria (ISTORIA: Jurnal Pendidikan dan Sejarah, 2011)
Abstract This research was to elaborate the big battles between Greece and Persian in the past called by historian as Persian War. The civilization was one of the most influential factors as source of conflict in the past. The art, philosophy, and technologies by which Greece people were highly endeavors for humankind for several centuries. On the contrary, Persians civilization will be masterpiece for Eastern world. Darius, king of Persians, was the ambitious man, wishes to conquer West Asian and Greece to aggrandize her emporium and brought the Persian into the biggest in the world. This research use of historical method involving four steps: heuristic, critic, interpretation and historiography. The researcher use Herodotus book (Histories) to describe the Persian War and comparing with another source such as: paper from Kevin Wheeler. Afterward I analyze with the clash of civilization by which introduce by Huntington. Samuel P Huntington made a hypothesis that the fundamental source of conflict in this new world will not be primarily ideological or primarily economic. The great divisions among humankind and the dominating source of conflict will be cultural. The Persian War was took place in 490-480 BC represent of this hypothesis. Keywords: the Clash of civilization, Persian War.